2001
DOI: 10.1097/00004647-200111000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Prosaposin-Derived, 18-Mer Peptide on Slowly Progressive Neuronal Degeneration after Brief Ischemia

Abstract: Summary:Slowly progressive degeneration of the hippocampal CA1 neurons was induced by 3-minute transient global ischemia in gerbils. Sustained degeneration of hippocampal CA1 neurons was evident 1 month after ischemia. To investigate the effects of an 18-mer peptide comprising the hydrophilic sequence of the rat saposin C domain (18MP) on this sustained neuronal degeneration, an intracerebroventricular 18MP infusion was initiated 3 days after ischemia. Histopathologic and behavior evaluations were conducted 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…For example, the infusion of prosaposin into the lateral ventricles of gerbils prior to the induction of ischemia was found to prevent learning disabilities resulting from ischemic damage (Sano et al, 1994). Similar results were found when an 18-amino-acid prosaptide was infused into the lateral ventricles of gerbils (Kotani et al, 1996b; Morita et al, 2001). These behavioral effects were found to be accompanied by cellular changes consistent with protection of cells from apoptotic death (Morita et al, 2001; Sano et al, 1994).…”
Section: Effects Of Secreted Prosaposin In the Nervous Systemsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, the infusion of prosaposin into the lateral ventricles of gerbils prior to the induction of ischemia was found to prevent learning disabilities resulting from ischemic damage (Sano et al, 1994). Similar results were found when an 18-amino-acid prosaptide was infused into the lateral ventricles of gerbils (Kotani et al, 1996b; Morita et al, 2001). These behavioral effects were found to be accompanied by cellular changes consistent with protection of cells from apoptotic death (Morita et al, 2001; Sano et al, 1994).…”
Section: Effects Of Secreted Prosaposin In the Nervous Systemsupporting
confidence: 81%
“…Similar results were found when an 18-amino-acid prosaptide was infused into the lateral ventricles of gerbils (Kotani et al, 1996b; Morita et al, 2001). These behavioral effects were found to be accompanied by cellular changes consistent with protection of cells from apoptotic death (Morita et al, 2001; Sano et al, 1994). The infusion of the 18-amino-acid prosaptide into the lateral ventricles or the injection of the retro-inverso prosaptide D5 were also able to prevent secondary degeneration in the thalamus following occlusion of the left middle cerebral artery (Igase et al, 1999; Lu et al, 2000).…”
Section: Effects Of Secreted Prosaposin In the Nervous Systemsupporting
confidence: 81%
“…However, it was unclear from these earlier studies whether these severe inner ear deficits were due to the actions of prosaposin itself, which is known to have intrinsic nerve growth factor–like qualities, or one of its cleaved end products, saposin A–D. In an attempt to answer this question, two transgenic mice, one carrying a null mutation of saposin C, and a second carrying a combined null mutation of saposin C and D, were studied .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that prosaposin prevents nerve degeneration and promotes nerve regeneration in animal models of nerve injuries, including a strong protective action against ischemic and wound stab damage of hippocampal neurons (24,30,43,54). The relative abundance of the exon 8-containing prosaposin isoform was recently shown to sharply decline following ischemia and stab wound in rat brain (19).…”
Section: Vol 25 2005 Exon 8-containing Prosaposin Gene Splice Variamentioning
confidence: 99%